(untitled) (Modern education and development, 2025)
As is known, poetic syntax deals with sentence structure and the order of sentence parts in the lines, couplets, and stanzas of poetry. In poetic speech, the construction of poetic sentences, word choice, and their skillful use in sentence structure are of great importance[1]. The poetic syntax of each creator’s poems stands out with its uniqueness. [1] Бобоев Т. Адабиётшунослик асослари. Т.: - Ўзбекистон, 2002. Б.423.